Type 2 Decompression Sickness in a Traditional Diver: A Case Report and Treatment with Hyperbaric Oxygen Therapy - Bendy Dwi Irawan (Jurnal Ragam Pengabdian, 2026)
Decompression sickness (DCS) type 2 is a medical emergency frequently experienced by traditional divers due to inadequate diving procedures. Hyperbaric Oxygen Therapy (HBOT) is the definitive standard treatment for DCS with neurological manifestations. This case report describes the management of a 37-year-old male patient who developed type 2 DCS after diving to a depth of 30 meters for two hours using a compressor. The patient underwent staged HBOT using the US Navy Table 6, Table 5, and Kindwall Table protocols at a pressure of 2.8 ATA at RSAL dr. Wahyu Slamet Bitung from June 14 to June 21, 2025. Neurological evaluation was performed using the Neurological Deficit Score (NDS) before and after therapy. The patient showed significant neurological improvement after eight HBOT sessions within eight days, as indicated by a decrease in NDS from 8 to 2 and improvement in lower extremity motor strength from 2/5 to 5/5. Neurological symptoms, including limb weakness, muscle cramps, and urinary retention, gradually improved, with meaningful clinical improvement beginning at the seventh therapy session and complete recovery achieved after the eighth session. Hyperbaric oxygen therapy using a staged protocol was effective in managing type 2 DCS with severe neurological manifestations in traditional divers. Early management using an appropriate therapeutic protocol resulted in excellent clinical outcomes with complete neurological functional recovery.